2021
DOI: 10.1002/mrc.5185
|View full text |Cite
|
Sign up to set email alerts
|

Application of aromatic amide‐derived atropisomers as chiral solvating agents for discrimination of optically active mandelic acid derivatives in 1H nuclear magnetic resonance spectroscopy

Abstract: Non‐biaryl atropisomers and their stereochemistry have attracted much attentions in the past years. However, application of the non‐biaryl atropisomers as chiral solvating agents is yet to be explored. In this work, four aromatic amide‐derived atropisomeric phosphine ligands (hosts) were used as chiral solvating agents to recognize various mandelic acid derivatives (guests) in 1H nuclear magnetic resonance (NMR) spectroscopy. It is found that chiral center configurations of the four hosts have different effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“… DFT calculations of 1 H-, and 13 C- chemical shifts and J couplings can contribute significantly to the unequivocal resonance assignment, identification of cis / trans geometric isomers, and diastereomeric pairs of complex hydroperoxides and solvent effects [ 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 198 , 199 ]. Further, research is also required for the determination of chirality in solution [ 200 ]. Development of officially recognized NMR methodologies for LOOHs in fats and oils through collaboration of various NMR groups.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“… DFT calculations of 1 H-, and 13 C- chemical shifts and J couplings can contribute significantly to the unequivocal resonance assignment, identification of cis / trans geometric isomers, and diastereomeric pairs of complex hydroperoxides and solvent effects [ 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 198 , 199 ]. Further, research is also required for the determination of chirality in solution [ 200 ]. Development of officially recognized NMR methodologies for LOOHs in fats and oils through collaboration of various NMR groups.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…The role of salification processes in the mechanism of interaction between CSA I and enantiomeric substrates has been fully confirmed through the analysis of mixtures containing substrates 2-bromopropionate (28) and valine methyl ester hydrochloride (29) (Figure 2). Both substrates 28 and 29, devoid of free carboxylic functions, did not dissolve compound I.…”
Section: Interaction Mechanismmentioning
confidence: 83%
“…The remarkable significance of chiral carboxylic acids as constituents of numerous natural products and pharmaceutically relevant compounds has spurred the development of CSAs for NMR spectroscopy, primarily aimed at enantiodiscrimination within this compound class [4][5][6][7][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, our group found that the four aromatic-amide-derived atropisomers 57 shown in Scheme could act as chiral solvating agents to recognize structurally diverse mandelic acid derivatives (12 examples) in 1 H NMR spectroscopy, where the stereogenic configurations of these atropisomers (hosts) have different effects on the stereoselective recognition of the mandelic acid derivatives used (guests) . For example, anti -( R , R s)- 57a displayed better recognition of most guests except for the electron-withdrawing mandelic acid derivatives.…”
Section: Merging Non-biaryl Atropisomers With Point Chiralitymentioning
confidence: 99%